The β2-adrenergic biased agonist nebivolol inhibits the development of Th17 and the response of memory Th17 cells in an NF-κB-dependent manner - Hajiaghayi, Mehri; Gholizadeh, Fatemeh; Han, Eric; Little, Samuel R.; Rahbari, Niloufar; Ardila, Isabella; Lopez Naranjo, Carolina; Tehranimeh, Kasra; Shih, Steve C. C.; Darlington, Peter J. (Frontiers in Immunology, 2024)
Introduction: Adrenergic receptors regulate metabolic, cardiovascular and immunological functions in response to the sympathetic nervous system. The effect of β2-adrenergic receptor (AR) as a highexpression receptor on different subpopulations of T cells is complex and varies depending on the type of ligand and context. While traditional β2-AR agonists generally suppress T cells, they potentially enhance IL-17A production by Th17 cells. The effects of pharmacological drugs that count as biased agonists of AR like nebivolol are not completely understood. We investigated the impact of nebivolol on human memory CD4+ T (Th1, Th2, Th17) cells and polarized naïve Th17 cells highlighting its potential for IL-17A suppression via a non-canonical β2AR cell-signaling pathway.The effects of nebivolol were tested on healthy human peripheral blood mononuclear cells, purified memory Th cells, and polarized naïve Th17 cells activated with antiCD3/antiCD28/antiCD2 ImmunoCult reagent. IFN-g, IL-4, and IL-17A which are primarily derived from Th1, Th2, and Th17 cells respectively, were quantified by ELISA and flow cytometry. IL-10 was measured by ELISA. Gene expression of RORC, ADRB1, ADRB2, and ADRB3 was evaluated by qPCR. The ADRB2 gene was knocked out in memory Th cells using CRISPR/Cas9. Protein expression of phosphorylated-serine133-CREB and phosphorylated-NF-κB p65 was assessed by Western blot. Proliferation was assessed by fluorescent dye loading and flow cytometry.Results: Nebivolol treatment decreased IL-17A and IFN-γ secretion by activated-memory Th cells and elevated IL-4 levels. Nebivolol reduced the proportion of IL-17A+ Th cells and downregulated RORC expression. Unlike the β2-AR agonist terbutaline, nebivolol inhibited the shift of naïve CD4+ T cells towards the Th17 phenotype. IL-10 and proliferation index remained unchanged. Nebivolol-treated β2knockout memory Th cells showed significant inhibition of β2AR-mediated signaling, evidenced by the absence of IL-17A suppression compared to controls. Phosphorylation of the NF-κB p65 subunit was inhibited by nebivolol, but CREB phosphorylation was not changed, suggesting a selective transcriptional control.The findings demonstrate that nebivolol acts through a β2-AR-mediated signaling pathway, as a distinctive anti-inflammatory agent capable of selectively shifting Th17 cells and suppressing phosphorylation of NF-κB. This highlights nebivolol's potential for therapeutic interventions in chronic autoimmune conditions with elevated IL-17A levels.